Pengaruh Komunikasi dan Lingkungan Kerja Terhadap Kinerja Karyawan dengan Kepuasan Kerja Pada CV Citra Dragon Teknik - Silvira Ananda Sutri (CV. ITTC INDONESIA, 2026)
This research aims to analyze the influence of Communication and Work Environment on Employee Performance with Job Satisfaction in CV Citra Dragon Teknik. The problem in this research is based on the failure to achieve the production target by Employee Performance, which is suspected to be influenced by the way of communication, work environment conditions and perceived job satisfaction. This research uses a quantitative approach with the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. Data collection technique is carried out through the distribution of questionnaires to all employees of CV Citra Dragon Teknik with as many as 30 respondents. Data analysis is done with the help of SmartPLS 4.0 software to test the direct and indirect influence between variables. The research results show that Communication has a positive and significant effect on Job Satisfaction, and the Work Environment has a positive and significant effect on Job Satisfaction. In addition, Communication has a positive and significant effect on Employee Performance, but the Work Environment does not have a significant effect on Employee Performance. Furthermore, Job Satisfaction does not have a significant effect on Employee Performance. The mediation test on the structural model shows that Job Satisfaction significantly mediates the influence of Communication on Employee Performance, while Job Satisfaction does not significantly mediate the influence of the Work Environment on Employee Performance.